Transformational Leadership Contribution To Increase Motivation and Employee Discipline Through ASN Management Application System - Vista Dwi Andani; Hayat Hayat; Retno Wulan Sekarsari (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The existence of the application of a transformational leadership style by the leadership of the Malang City BKPSDM has made various implementations from the management side of the State Civil Apparatus now having to start adapting to the programs that have been made such as the implementation of the ASN Management Application System. One of the obstacles faced by the implementation of the ASN Management Application System is that there are many elderly ASNs who did not yet have technology in their era, so they still do not understand the ASN management application system. From these reasons, the authors wanted to compile research with the aim of knowing and analyzing the contribution of the Malang City BKPSDM transformational leadership in increasing employee motivation and discipline through the ASN management application system. The research method used by the author is a qualitative method. The results of this study are that the transformational leadership contribution of the Head of BKPSDM Malang City in increasing employee motivation and discipline through the ASN management application system has been going well and as it should. Apart from that, there are also several obstacles such as the adaptation of employees who are still not good and the application system which crashes several times, there is maintenance so that employees cannot use the application.